(untitled) (Economic and Political Thought, 2013)
From 1 July 2013 the Republic of Lithuania will start its first presidency of the Council of the European Union. Since the Treaty of Lisbon came into force, Lithuania will participate in the third trio-presidency. It will also be the fifth presidency of a member state that joined the European Union in 2004. The subject matter of the six-month research, the results of which are presented in the present work, was Lithuania’s preparation for its first presidency of the Council and the course of research was determined by the following research questions: In what way will the changes introduced to the European Union system of institutions by the Treaty of Lisbon as well as the practice of former presidencies influence the Lithuanian presidency? In what way will the preparation to presidency influence the Europeanization of the Lithuanian administration and the system of the European policy coordination? How does the Lithuanian government publicize the approaching presidency? Are there any working meetings between Poland and Lithuania in order to exchange information about good practices? What may be the priorities of the Lithuanian presidency? What can affect them? Moreover, we asked the following questions regarding priorities: To what extent can Lithuania use the presidency of the Council to promote and satisfy its own interests at the European level? What will be the relationship between the European Union and national interests? Which countries, especially Baltic ones, will Lithuania cooperate with in the priority areas? Having taken into account the preparations to presidency so far, is it possible to predict if the Lithuanian presidency will be reliable, efficient and effective?